Rock 'n' labels: Tracking the Australian recording industry in 'The Vinyl Age': Part One, 1945-1970 - Walker, C.; Hogan, T.; Beilharz, Peter (2012)
Over the past 50 years, rock music has been the prime mover of an emergent national recording industry in Australia. In this study, which has two parts, we survey record labels, recording techniques and forms, and the music that was bought and sold. Part One narrates the emergence of modern record production, the rise of rock music, and the development of a local recording industry in Australia between 1945 and 1970. Part Two (to be published in Thesis Eleven 110) recounts the rise and fall of Australian local, regional and national rock music cultures and the ebb and flow of independent labels and their labyrinthine relations to the transatlantic centre of the world-system of the rock music industry. In particular, we focus on four aspects: technological change, infrastructure, business logistics/markets, and musical production/repertoire. Since the digital revolution started eating away firstly and most conspicuously at the recording industry, the 50 years from 1945 to 1995 can now more clearly be seen as the rise and fall of rock music and its major technological form, the vinyl record. This is why we call it 'the vinyl age'. This story has not been told in full previously, and this two-part article is a first step to bridge this gap in the historical and cultural sociology of popular music. © The Author(s) 2012.